Deploying charging infrastructure for electric vehicles; viability analyses for municipal and private car parking facility operators - Vannieuwenborg, Frederic; Tahon, Mathieu; Verbrugge, Sofie; Colle, Didier; Pickavet, Mario; Demeester, Piet (European Journal of Transport and Infrastructure Research, 2014)
A lot of research has been done on the adoption of electric vehicles and on the deployment of the infrastructure for charging the batteries of these vehicles. Currently the total number of installed charging points keeps growing due to both public and private investments. Often charging services are offered as free service extensions. Maintaining this free business model will be difficult on the long term because of the investments needed. Therefore, the long term business viability and durability is not always clear from an investor point of view. This work presents a techno-economic model that describes the expected cost and revenue evolution resulting from different deployment strategies for a municipal or private parking facility operator. For charging service providers, charging pole exploiters and infrastructure owners for electric vehicle charging, the model allows to project the expected profitability. The main findings from this research indicate that business cases for public charging infrastructure can be viable, durable and could be competitive with the costs for charging the electric vehicle at home. Also, in a multi-actor market model all actors involved could benefit from deploying electric vehicle charging infrastructure. Although the business cases will be positive, significant investments are needed.